Second Order Systems : Beating in Undamped Systems - Peters, Diane L. (McGraw-Hill's AccessEngineering., 2019)
This video explains the response of a second order system to a step input with various types of damping - undamped, underdamped, critically damped, and overdamped. It uses a mass-spring-damper system to show the response for each of these conditions and relates the system response to the eigenvalues of the system.